2019
DOI: 10.1016/j.hpb.2019.10.615
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide prospective audit of pancreatic surgery: design, accuracy, and outcomes of the Dutch Pancreatic Cancer Audit

Abstract: Background: Pancreatic cystic neoplasms include serous tumors, pseudopapillary neoplasms mucinous tumors, and IPMN. Sendai criteria, last update Fukuoka criteria, have increased attention on IPMN. Methods: We retrospectively reviewed patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 0 publications
1
48
0
Order By: Relevance
“…PD is considered a complex surgical procedure and associated with significant postoperative morbidity and mortality, even in modern series. [1][2][3] The long-term survival from surgery is very limited for adenocarcinoma, 4 and uncertain for cystic neoplasms, 5 and quality-of-life following PD can be substantially impaired. 6,7 Therefore, it is important that short term outcomes are monitored and optimized if such surgery is to be justified.…”
Section: Introductionmentioning
confidence: 99%
“…PD is considered a complex surgical procedure and associated with significant postoperative morbidity and mortality, even in modern series. [1][2][3] The long-term survival from surgery is very limited for adenocarcinoma, 4 and uncertain for cystic neoplasms, 5 and quality-of-life following PD can be substantially impaired. 6,7 Therefore, it is important that short term outcomes are monitored and optimized if such surgery is to be justified.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported a high quality of DPCA data. 36 In conclusion, this nationwide study found that EBD prior to pancreatoduodenectomy still frequently involved plastic stents. SEMS placement seemed to be associated with lower risks of cholangitis, less postoperative pancreatic fistula, and a shorter postoperative hospital stay but not with an increased risk of pancreatitis.…”
Section: Discussionmentioning
confidence: 61%
“…During follow-up, serum and EDTA plasma samples are collected at the first postoperative visit to the out-patient clinic, 6 months, 12 months, and 24 months postoperatively, and at recurrence. Data are collected in conjunction with the Dutch Pancreatic Cancer Audit 6 and via Castor Electronic Data Capture (Amsterdam, the Netherlands). Researchers can submit a study proposal for use of the samples to the scientific committee (pancreasparel@dpcg.nl) of the Dutch Pancreatic Cancer Group.…”
Section: Dutch Pancreas Biobankmentioning
confidence: 99%
“…For this study additional data regarding preoperative imaging and biomarker characteristics (location of the tumor, tumor diameter, clinical lymph node status, and venous and arterial involvement on imaging, and bilirubin level in clinical laboratory) were obtained via the Dutch Pancreatic Cancer Audit. 6 All data were retrieved from medical records by a trained research nurse or MD.…”
Section: Definitionsmentioning
confidence: 99%